2017
DOI: 10.1016/j.micpath.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Melaleuca alternifolia essential oil prevents alterations to purinergic enzymes and ameliorates the innate immune response in silver catfish infected with Aeromonas hydrophila

Abstract: Aeromonas hydrophila infection represents a major impediment to the development of aquaculture, leading to important economic losses. Over the last few years, different methods have been used to counteract and minimize the negative effects of this infection, such as the use of Melaleuca alternifolia essential oil, popularly known as tea tree oil (TTO), that possess a bactericide action against A. hydrophila. The purinergic system develops an important role in the inflammatory response, principally due to invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The upregulation of splenic NTPDase activity may be related to a compensatory organic response or to an important physiological adjustment of the nucleotidase pathway to hydrolyse the excessive ATP in the extracellular environment, in agreement with the observations of Baldissera, Souza¸ Doleski et al. () in serum samples of silver catfish experimentally infected with A. hydrophila . It is important to emphasize that excessive extracellular ATP levels can interact with type P2 purine receptors to induce the release of proinflammatory cytokines and reduce the release of anti‐inflammatory cytokines (Borowiec, Lechward, Tkacz‐Stachowska, & Skladanowski, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The upregulation of splenic NTPDase activity may be related to a compensatory organic response or to an important physiological adjustment of the nucleotidase pathway to hydrolyse the excessive ATP in the extracellular environment, in agreement with the observations of Baldissera, Souza¸ Doleski et al. () in serum samples of silver catfish experimentally infected with A. hydrophila . It is important to emphasize that excessive extracellular ATP levels can interact with type P2 purine receptors to induce the release of proinflammatory cytokines and reduce the release of anti‐inflammatory cytokines (Borowiec, Lechward, Tkacz‐Stachowska, & Skladanowski, ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the immunological pathways involved in the immune response during A. caviae infection remain unknown. Therefore, we decided to evaluate the activities of enzymes belonging to the purinergic system, which play a fundamental role in fish immunity (Baldissera, Souza¸ Doleski et al., ; Cekic & Linden, ).…”
Section: Introductionmentioning
confidence: 99%
“…This EO also prevents oxidative damage in liver proteins and lipids, as well as maintaining the purinergic system (Baldissera et al . ,). The use of the EOs of H. ringens and O. americanum in preventive baths increased the complement system activity compared with control, but there was no significant difference in survival of silver catfish challenged with Aer.…”
Section: In Vivo Assays With Eos As Antibacterial Agents In Fishmentioning
confidence: 99%
“…Terpene content of the BM may be responsible for this. Previously, Baldissera et al (2017) demonstrated an increased transcription of IL‐6 in catfish treated with Melaleuca alternifolia essential oil. They also correlated that the elevated IL‐6 gene must be related to the terpene content of the oil.…”
Section: Discussionmentioning
confidence: 95%